Retraction Note: Identify and measure the degree of over-prevention behaviors in the post-COVID-19 era in China - Rongyang Ma; Hong Wu; Zhaohua Deng (BMC Public Health, 2021)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12889-021-12352-w